Diferentes fontes proteicas em rações de leitões sobre atividade da tripsina e parâmetros sangüíneos - Thomaz, Maria Cristina [UNESP]; Hannas, Melissa Izabel; Tucci, Fernanda Marcussi; Scandolera, Antônio João; Loddi, Maria Marta; Budiño, Fábio Enrique Lemos (My University, 2009)
Were used 64 piglets submitted eight treatments: ration with skim milk (SM), three rations with crescent levels of swine plasma (SP), three rations with whole egg (WE) and a ration with high inclusion of soybean meal (SB). Were monitored the blood parameters (BP) in pigs at 27 and at 34 days of age. The piglets were slaugther at 28 and at 35 days of age, for collections pancreas and posterior mensurements of absolut (AW) and relative weigth (RW) of pancreas and trypsin activity (TA). Treatments not influencied AW and TA. Significant effect of the crescent levels was verified of SP, with lineal reduction of the leukocytes and increase of the globular volume, to the 27 days; while to the 34 days, lineal increase of the hematias was observed. At 27 days, animals feds rations with crescent levels of SP have inferior percentage of eosinophils than others that consumed crescent levels of WE. The utilization of SP promoted smaller stimulus to the immune reply, while the use of WE promoted larger humoral reply of the piglets.
Different protein sources in rations of piglets on activity of trypsin and blood parameters
Keywords: Digestive enzyme; Hematia; Leukocyte; Nutrition; Swine; Animalia; Glycine max; Suidae